Clinical features, risk factors, diagnosis, and treatment of trimethoprim-sulfamethoxazole-induced hypoglycemia - Wang, Chunjiang; Fang, Weijin; Li, Zuojun; Sun, Linli (Frontiers in Endocrinology, 2023)
Objective Hypoglycemia is a sporadic and serious adverse reaction of trimethoprim-sulfamethoxazole (TMP-SMX) due to its sulfonylurea-like effect. This study explored the clinical characteristics, risk factors, treatment, and prognosis of TMP-SMX-induced hypoglycemia. Methods Case reports and series of TMP-SMX-induced hypoglycemia were systematically searched using Chinese and English databases. Primary patient and clinical information were extracted for analysis. Results A total of 34 patients were reported from 31 studies (16 males and 18 females). The patients had a median age of 64 years (range 0.4-91), and 75.8% had renal dysfunction. The median duration of a hypoglycemic episode was six days (range 1-20), and the median minimum glucose was 28.8 mg/dL (range 12-60). Thirty-two patients (97.0%) showed neuroglycopenic symptoms, with consciousness disturbance (30.3%) and seizure (24.2%), sweating (18.2%), confusion (15.2%), asthenia (12.1%) being the most common symptoms. Fifteen patients (44.1%) had elevated serum insulin levels, with a median of 31.8 μU/mL (range 3-115.3). C-peptide increased in 13 patients (38.2%), with a median of 7.7 ng/mL (range 2.2-20). Complete recovery from symptoms occurred in 88.2% of patients without sequelae. The duration of hypoglycemia symptoms was 8 hours to 47 days after the intervention. Interventions included discontinuation of TMP-SMX, intravenous glucose, glucagon, and octreotide. Conclusion Hypoglycemia is a rare and serious adverse effect of TMP-SMX. Physicians should be aware of this potential adverse effect, especially in patients with renal insufficiency, increased drug doses, and malnutrition.